The principles of targeting applied to maternal health care services in urban poor communities - Ferrer, Alice Joan G. (Miag-ao UP Visayas, 2005)
"This paper applies the principles of targeting to the maternal health care program for women in urban poor communities. The targeting problem is presented, highlighting the informational and administrative difficulties encountered in implementing the ideal solution of identifying all the target women. The challenge for policy is to design an efficient second best targeting scheme where targeting is done under imperfect/incomplete information. An offer is made with the use of targeting using indicators and increasing the incentives for women to voluntarily participate."
Keywords: Mothers -- Medical care